NIKAH SIRRI DALAM PERSPEKTIF YURIDIS DAN SOSIOLOGIS - nur wahidah (Universitas Islam Negeri Antasari Banjarmasin, 2016)
Married siri is carried out by the community, with various shapes and reasons. Scholars who allow their marriage Sirri when harmony and marriage requirements are met, the opportunity for most citizens of the community to do this practice, even in another form that ignores harmony and the terms of the wedding itself. When the mayor is absent or does not approve, they were reluctant to marry guardian judge, but chose to do it Sirri marriage outside legal procedures. They forget that marriage is a strong bond, which binds husbands and wives inwardly and outwardly with certain consequences, both to the couple itself and to children offspring.